2011
DOI: 10.1177/1077801211434725
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Detectives’ Manner of Questioning on Rape Victims’ Disclosure

Abstract: Research has documented that few reported rapes are prosecuted by the legal system. The purpose of this study is to explain how the interactions between victims and detectives can strengthen or weaken the investigation itself. Twenty rape victims were interviewed to examine how law enforcement detectives' manner of questioning affects rape victims' level of disclosure. Using qualitative methodology, the results show that the detectives' manner of questioning can play a role in victims' disclosure. Detectives u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 24 publications
8
81
1
Order By: Relevance
“…or "Why didn't you fight back?" (see Patterson, 2011). This is consistent with research from Myhill and Johnson (2016).…”
Section: Legal and Policy Interventionssupporting
confidence: 90%
“…or "Why didn't you fight back?" (see Patterson, 2011). This is consistent with research from Myhill and Johnson (2016).…”
Section: Legal and Policy Interventionssupporting
confidence: 90%
“…Even specialist training on the issue has not been found to impact on police Officers' rape victim blaming (Sleath & Bull, 2012). Positive or negative experiences at disclosure can impact on the judicial process, and is important in relation to victim blaming and victim believability (Patterson, 2011). If an already vulnerable victim discloses and is not believed, and blamed for her/his own victimisation then this has an 16 adverse impact on that individual (Patterson, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Positive or negative experiences at disclosure can impact on the judicial process, and is important in relation to victim blaming and victim believability (Patterson, 2011). If an already vulnerable victim discloses and is not believed, and blamed for her/his own victimisation then this has an 16 adverse impact on that individual (Patterson, 2011). Given the present findings, combined with literature indicating that victim blaming occurs within the police, further research into whether the fact that many staff involved in receiving rape/revenge pornography victim reports are male deters victims from reporting an offence, or re-traumatises the victim, is an area that would benefit from further research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooperation was less likely if the victim was under the influence of alcohol or drugs or had a history of drug use Tellis & Spohn, 2008). A qualitative study by Patterson (2011) examined the ways in which victims' interactions with detectives during a rape investigation influenced their level of disclosure. This Downloaded by [Gazi University] at 07:24 30 December 2015 study found that victims who perceived the detective's manner of questioning to be gentler provided more information.…”
Section: Victim Decision Makingmentioning
confidence: 99%